Real-time Spatiotemporal Stereo Matching Using the Dual-Cross-Bilateral Grid - Richardt, Christian; Orr, Douglas A. H.; Davies, Ian P.; Criminisi, Antonio; Dodgson, Neil A. (European Conference on Computer Vision (ECCV), 2010)
We introduce a real-time stereo matching technique based on a reformulation of Yoon and Kweon’s adaptive support weights algorithm. We use the bilateral grid to achieve a speedup of 200× compared to a straightforward full-kernel GPU implementation, making our technique the fastest on the Middlebury website. Based on our technique, we present a spatiotemporal stereo matching approach that incorporates temporal evidence in real time (>14 fps). Our technique visibly reduces fl ickering and outperforms per-frame approaches in the presence of image noise.